On Proper Names in German: An Analysis from the Cognitive Perspective - Majcher, Magdalena Zofia Zofia (Respectus Philologicus, 2013)
The aim of this paper is a cognitive grammar analysis of noun phrases in German which contain a proper noun. It is common for proper nouns in German, like first names, surnames, the names of cities and countries, to occur without an article. They can, however, also occur with the definite article, the demonstrative pronoun or with the indefinite article. There are also proper nouns in German, such as the names of rivers, mountain ranges, and some countries, which—according to many grammars—obligatorily occur with the definite article. However, it may happen that even those occur without an article. Whether there is an article before a proper noun or not is regarded as a grammatical phenomenon, without acknowledging its semantic aspects. The latter are only considered in a very few cases. A cognitive grammar analysis makes it possible to look at the abovementioned phenomena from the semanticconceptual perspective, thus ensuring wider opportunities to explain and describe them. According to cognitive grammar, every use of any element should have a semantic-conceptual motivation. The cognitive grammar analysis of German noun phrases containing a proper noun carried out in this article allows us to conclude that the use of articles in the German language is in most cases determined by the speaker’s intention. The analysis in this paper includes a description of noun phrases containing proper nouns selected from the German magazine Der Spiegel.
Keywords: Cognitive Grammar; Noun Phrase; Proper Names; German Articles